Physical and chemical characteristics of pyrogenic carbon from peatland vegetation fires differ across burn severities - Kennedy-Blundell, Oscar J.; Shuttleworth, Emma L.; Rothwell, James J.; Clay, Gareth D. (Frontiers in Earth Science, 2025)
IntroductionVegetation fires lead to the formation of charred materials, often referred to as pyrogenic carbon (PyC), which are recalcitrant and have a high carbon densitymeaning they have the potential to act as a long-term carbon store. In the United Kingdom, peatlands are periodically subject to fire, both management burns and wildfires, which generate PyC. However, in the United Kingdom context, the characterisation of physical and chemical properties of PyC is limited.MethodsIn this study, samples of peatland vegetation (Calluna vulgaris, Polytrichum juniperinum, Vaccinium myrtillus and Eriophorum vaginatum) were burnt in laboratory conditions across typical ranges of characteristics from United Kingdom peatland vegetation fires (250°C–800°C and 2–10 min burn duration). Four broad severity groupings were established (low, moderate, high, very high) corresponding to 60, 70, 80% and 90% mass loss respectively. The PyC samples were then analysed using Brunauer-Emmett-Teller (BET) surface area analysis, CHNO elemental analysis, and Fouriertransform infrared spectroscopy (FTIR) to gain a greater understanding of their physiochemical characteristics.ResultsWhile there was a good degree of similarity between samples within each severity group, there were significant differences between severity groups. Low to high severity samples had relatively low surface areas compared to the very high severity samples, which exhibited the greatest surface areas and a high degree of variability. O/C and H/C ratios decreased with increasing severity. FTIR showed that distinct spectra were produced between severity groups, reflecting increased sample aromaticity with burn severity.DiscussionThe findings of this study suggest that burn severity is a good predictor of PyC physiochemical characteristics.